Application Development of E-Commerce Business Intelligence Dashboard - Prakoso, Muhammad Naufal; Nuryuliani, (International Journal of Computer Sciences and Engineering, 2019)
Application of Business intelligence produces information that can be used as decision support. Companies in the E-Commerce require business intelligence applications to manage existing data to be useful. Manager using this information for decision in strategy or staff for operational support. In this study, researchers created a business intelligence dashboard application that can be used as a reference for e-Commerce companies in processing raw data to become useful information for decision. Development of business intelligence application based on business intelligence architecture. The business intelligence architecture consists of data source, ETL, data warehouse, Dashboard and BI users. Business Intelligence Application is created using Dashboard to display information. The results of this study are business intelligence dashboard application which has four dashboard options for e-Commerce companies. The summary dashboard displays a summary of information. The customer dashboard displays information based on the customer. The product dashboard displays information based on the product. Transaction dashboard displays information based on transaction. Module testing on dashboard is done using black box testing, the test results on four dashboards in the application, can function correctly.